2023
DOI: 10.1891/jnm-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Post Event-Cardiovascular Risk Perception Survey: Validity and Reliability in Cardiac Patients Post Heart Event

Kathy Prue-Owens,
Keston Lindsay,
Helen Graham
et al.

Abstract: Background:Cardiac risk perception in patients who had a heart event is unknown.Purpose:Evaluate the validity and reliability of the Post Event-Cardiovascular Risk Perception Survey (PE-CRPS).Methods:This is a descriptive, cross-sectional study with a convenient sample of 251 patients who experienced a heart event. Descriptive and exploratory factor analyses was used to analyze the data.Results:Nine of ten items with an oblique (direct oblimin) rotation resulted in two factors extracted, which explained 54% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…instrument called Post Event-Cardiovascular Risk Perception Survey (PE-CRPS) among hospitalized inpatient and outpatient cardiac rehabilitation patients who had a known history of heart disease. Although individual patient demographic information was not collected, the study found the PE-CRPS reliable and valid but more importantly, participants did not indicate a risk for developing further CVD [27].…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…instrument called Post Event-Cardiovascular Risk Perception Survey (PE-CRPS) among hospitalized inpatient and outpatient cardiac rehabilitation patients who had a known history of heart disease. Although individual patient demographic information was not collected, the study found the PE-CRPS reliable and valid but more importantly, participants did not indicate a risk for developing further CVD [27].…”
Section: Resultsmentioning
confidence: 86%
“…Data analyses were performed using IBM SPSS Statistics (Version 27) [46]. The reliability was examined using Cronbach's Alpha coefficients and component relationships similar to the study conducted by Prue-Owens and colleague [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations